Empirical modeling of material composition and size in MOFs prepared with ligand mixtures. Issue 9 (8th February 2019) - Llabrés-Campaner, Pedro J.; Zaragozá, Ramón José; Aurell, María José; Ballesteros, Rafael; Abarca, Belén; García-España, Enrique; Rodrigo, Guillermo; Ballesteros-Garrido, Rafael
Abstract : MixedMOF-5 /IRMOF-3 case study: from micrometers to millimeters. Abstract : Systematic analyses of the composition and size of metal–organic frameworks built with Zn4 O and terephthalic/amino-terephthalic acid mixtures, together with a kinetic assay, reveal how these ligands behave differently, which reveals the complexity of crystal growth in these frameworks and the ability to tune it on purpose.